THE DEVELOPMENT OF STUDENT'S CULTURAL COMPETENCE IN A POST-INDUSTRIAL SOCIETY: THE IMPERATIVES OF CAPITAL APPROACH - Lyudmila V. Astakhova (National Research Mordova State University, 2017)
Introduction: problems of cultural competence development among higher school students are becoming increasingly important against a decline in a cultural level of an individual in a post-industrial society. Their relevance is determined by low level of effectiveness in the use of competence-based approach in higher education, debatable nature of the culture concept in scholarship, and evolution of axiological dominants in different cultures, specificity of dominant values in post-industr ial culture. Materials and Methods: the author uses a competence-based approach to determine the cultural competence of students. A cultural approach is applied to determine various approaches to culture. A capital approach is established as the approach enabling to take into account the cultural and axiological dominants of post-industrial society. Analytic-synthetic methods are used in the search and analysis of literature on the topic; the method of comparative analysis in the determination of essence of concepts of cultural competence: method of sociological survey to discover the level of cultural competence of graduates. Results: the sociological survey of employers revealed the insufficient level of cultural competence among graduates; the concept of cultural competence in pedagogical science was examined; the limitations of approaches to this concept were identified, the author's definition of cultural competence of personality in a postindustrial society is substantiated. Based on the author's informed definition of cultural competence, as well as the notion of cultural capital, the author substantiates the definition of "cultural-capital competence of a student in a post-industrial society" as a structural part of his / her cultural competence, which takes into account the requirements of a post-industrial society. Discussion and Conclusions: given the evolution of value priorities in a post-industrial culture, the author substantiates the imperatives of applying capital approach to the concept of cultural competence. The concept of cultural-capital competence is defined based on integration of competence with culturological approaches.